Mobile hotspot tethering and payment system using NFT - Ng, Warren Cin Yen (2023)
Internet access is one of the most crucial things nowadays. However, plenty of people are having excess cellular data at the end of the month. Therefore, this project aims to propose a solution to solve the problem of having excess cellular data. This project plans to develop a mobile hotspot tethering system with a payment system using NFT to help people deal with their excess cellular data. Users will be offered the ability to share their excess Internet access and be rewarded during the process. This mobile application will also implement blockchain and smart contracts in the payment system, providing users with a better way to interact and facilitating the token transaction process.